2021
DOI: 10.1093/rheumatology/keab729
|View full text |Cite
|
Sign up to set email alerts
|

MRP8/14 serum levels as diagnostic markers for systemic juvenile idiopathic arthritis in children with prolonged fever

Abstract: Objectives Differential diagnosis in children with prolonged fever is challenging. In particular, differentiating systemic-onset juvenile idiopathic arthritis (SJIA) from infectious diseases is difficult. Biomarkers are needed supporting the diagnostic work-up. The aim of this study was to validate the usefulness of MRP8/14 measurements in the diagnostic wok-up of febrile children and transfer it to clinical practice. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Patients diagnosed with macrophage activation syndrome (MAS) met the 2016 classification criteria for MAS complicating sJIA(37, 38). Serum samples were collected from sJIA patients (n=34; active disease (AD), n = 25; inactive disease (ID), n = 9) and pediatric HCs (n = 10) in course of a larger study as recently reported by us(39). Collective demographic and clinical characteristics are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients diagnosed with macrophage activation syndrome (MAS) met the 2016 classification criteria for MAS complicating sJIA(37, 38). Serum samples were collected from sJIA patients (n=34; active disease (AD), n = 25; inactive disease (ID), n = 9) and pediatric HCs (n = 10) in course of a larger study as recently reported by us(39). Collective demographic and clinical characteristics are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The absence of arthritis at the beginning of the disease is an impediment for clinicians, as there are currently no reliable diagnostic criteria, and this could lead to a delay in early positive diagnosis, which may have consequences for the initiation of targeted treatment, as well as patients’ outcomes and prognosis [ 17 , 18 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%
“…In children and adolescents with fever, but without treatment ( n = 195), serum concentrations of MRP8/14 in sJIA (19740 ± 5080 ng/mL) were much higher compared to other diagnoses, having the highest precision compared to all other parameters measured—such as ferritin, IL-18, ESR, soluble IL-2 receptor, and procalcitonin. The authors highlighted that serum tests of MRP8/14 can be useful for the positive diagnosis of sJIA in febrile patients, and commercial ELISA and LFIA allow accurate testing for rapid diagnostic screening at the point of care [ 18 ].…”
Section: Biomarkers For Diagnosis Treatment and Disease Activity In S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating biomarkers have been reported as potential biomarkers including but not limited to heme oxygenase-1, interleukin-6 (IL-6), IL-12, IL-18, osteoprotegerin, S100 calcium-binding protein A12 (S100A12) and S100A8/A9, among which only S100A8 and S100A9 were recently validated in a large cohort study of 1110 febrile pediatric patients and proposed to be the most promising biomarkers for sJIA diagnosis [7,8]. S100A8/9, with a cut off at 9160ng/ml, showed a 73% sensitivity and a 90% speci city in differentiating sJIA in fever of unknown origin among 195 untreated febrile pediatric patients.…”
Section: Introductionmentioning
confidence: 99%